2022
DOI: 10.1111/jam.15696
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of flavonoid-producing endophytic fungi from Loranthus tanakae Franch. & Sav that exhibit antioxidant and antibacterial activities

Abstract: Aims: Loranthus tanakae Franch. & Sav is a medicinal plant that has a variety of pharmacological properties. However, its study is currently limited because of its relative shortage of natural abundance. The objective of this work was to find an alternative resource from this plant that could produce its bioactive ingredients. Methods and Results: We isolated endophytic fungi from the twigs of Loranthus tanakae Franch. & Sav and eight flavonoid-producing endophytic fungi were selected. The eight endophytic fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Examining their biological properties showed that some of these compounds had strong alpha-glucosidase and lipase inhibitory activities and may act as natural anti-diabetic candidates. Zheng et al 33 succeeded in isolating eight endophytic fungi that produce flavonoid compounds from the branches of Loranthus tanakae and concluded that Alternaria tenuissima ZP28 and ZM148 have better anti-oxidant activity than others. Then, its flavonoid compounds were identified by LC–MS.…”
Section: Discussionmentioning
confidence: 99%
“…Examining their biological properties showed that some of these compounds had strong alpha-glucosidase and lipase inhibitory activities and may act as natural anti-diabetic candidates. Zheng et al 33 succeeded in isolating eight endophytic fungi that produce flavonoid compounds from the branches of Loranthus tanakae and concluded that Alternaria tenuissima ZP28 and ZM148 have better anti-oxidant activity than others. Then, its flavonoid compounds were identified by LC–MS.…”
Section: Discussionmentioning
confidence: 99%
“…Penicillium sp. LPV01 exhibited the highest similarity to P. lanosocoeruleum , a fungus isolated from various plants and soil ( 59 62 ). Therefore, it is likely that Penicillium sp.…”
Section: Discussionmentioning
confidence: 99%
“…To prepare the samples for metabolome detection, medicinal parts (i.e., ARH, ARB, and ART) were collected on an ultra-clean platform, cut into ~8 mm 3 pieces, mixed, and packed separately with 1 g per tube for cryopreservation. For endophytic fungi determination, the longer tissues were cut in the corresponding regions, and the surfaces were washed and disinfected, as previously described [ 26 , 27 ]. The tissues for the different parts were chopped and mixed evenly and then packed and frozen, 1 g per tube.…”
Section: Methodsmentioning
confidence: 99%